2014
DOI: 10.1371/journal.pone.0090444
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Multivariate Constraints to Evolution across Ten Long-Term Avian Studies

Abstract: BackgroundIn a rapidly changing world, it is of fundamental importance to understand processes constraining or facilitating adaptation through microevolution. As different traits of an organism covary, genetic correlations are expected to affect evolutionary trajectories. However, only limited empirical data are available.Methodology/Principal FindingsWe investigate the extent to which multivariate constraints affect the rate of adaptation, focusing on four morphological traits often shown to harbour large amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(99 citation statements)
references
References 74 publications
10
89
0
Order By: Relevance
“…Body mass has been found to be significantly heritable in the great reed warbler ( Acrocephalus arundinaceus ) as in many other passerine bird species23, and to be a highly evolvable trait23. In our data set, annual mid-parent and offspring body mass is significantly correlated irrespective of annual fluctuations in body mass, which supports the assumption that body mass has a significant heritable component in our population (Supplementary Fig.…”
Section: Resultssupporting
confidence: 86%
“…Body mass has been found to be significantly heritable in the great reed warbler ( Acrocephalus arundinaceus ) as in many other passerine bird species23, and to be a highly evolvable trait23. In our data set, annual mid-parent and offspring body mass is significantly correlated irrespective of annual fluctuations in body mass, which supports the assumption that body mass has a significant heritable component in our population (Supplementary Fig.…”
Section: Resultssupporting
confidence: 86%
“…See Table S1 for sample sizes Sequential model building involved testing with likelihood ratio tests (LRTs) (A) the effect of adding twoway interactions between year (coded as factor) and each of all traits and if found significant, then testing (B) the effect of each trait 9 year interaction independently of the other interactions Similar to our findings, the majority of these studies reported selection gradients that were negative for laying date, with earlier laying date being favourable, and positive for clutch size, with larger clutches being beneficial (e.g. different populations in Europe : Sheldon et al 2003;Garant et al 2007;Husby et al 2011b;Teplitsky et al 2011;Porlier et al 2012 Teplitsky et al 2014) being reported for these traits depending on the study system and species studied. Interestingly, the patterns of selection we documented here for morphological traitsselection favours heavier bird, does not affect wing length-are in contrast with the temporal phenotypic trends observed in our study system for females.…”
Section: Selection Patterns: Overall and Among Selection Episodessupporting
confidence: 75%
“…1, Table 4). This is in accordance to our expectations, because positive additive genetic covariance between these two traits has earlier been documented in house sparrows (Jensen et al, 2003) (non-significant in males), as well as in quantitative genetics studies of other bird species (Teplitsky et al, 2014). In contrast, neither the two bill traits nor body condition changed in response to correlated selection in the two experimental populations.…”
Section: Directional Selection and Variation In Individual Fitnesssupporting
confidence: 93%
“…In both populations tarsus length responded as expected in this heritable trait (Jensen et al, 2003Teplitsky et al, 2014). Additionally, wing lengths displayed a small significant correlated response.…”
Section: Main Results and Discussionsupporting
confidence: 68%